An Empirical Research on the Performance Analysis between Silicon and Quantum Computers - Aisar M.M.I, M.; S.M.Fauzi, S.; Baharin, H.; A.W.M. Sobri, W.; J. Suali, A.; A.JM. Gining, R.; N.F.Jamaluddin, M.; Helmy Abdul Wahab, Mohd (International Journal of Engineering and Technology, 2018)
This paper reports a preliminary study that compares the computational capabilities of silicon computers with quantum computers. Three types of programming control statements, for, while, and if-else were executed on a silicon computer and in Google Quantum Playground. Each control statements were executed five times or more in both computers and completion times were recorded. Average completion time was then calculated. The results show that silicon computers performed better that Google Quantum Playground.Â Â